Lorawan cattle tracking system - Heermandraj Naidu, Mokana Krishnan (2021)
For livestock care and natural resource management, an enhanced animal tracking system is needed. Commercially available tracking systems lack the data storage capacity required over long-term deployment periods to regularly collect animal location data. Most of them require high costs that cover from the purchase of the product to maintenance. As a result, monitoring and caring for animals has become a problem for many farmers. Therefore, most farmers used traditional ways of taking care of their animals where it was sometimes a huge burden for them, especially on a hectic day. Farmers, however, cannot constantly track the conditions of their livestock, even in usual or abnormal circumstances. This project therefore proposes a real-time Internet of Things (IoT) based cattle tracking device system that can play a key role in providing better animal care. The proposed system exploits sensors to animal tracking vital parameters such as GPS (Global Positioning System) tracker, water level sensor, humidity and temperature sensor. The design of the system consists of a GPS (Global Positioning System) tracker that locates the animals to prevent them from being lost. Next, the data recorded can be observed by farmers through The Things Network Gateway. Using the water level sensor, farmers can also monitor the surrounding condition of the cattle. If the enclosure cracks or breaks, the humidity and temperature sensor will monitor the air flow within the enclosure where we can detect leakages. As the main microcontroller, Arduino Uno is used to collect the information read by sensors and upload it to The Things Gateway. To allow farmers to easily locate their cattle, the data from The Things Network will be transferred to a mobile application. In order to prove its efficacy in terms of cost savings and energy efficiency, the proposed device prototype will be produced and tested so that farmers can track their animals anywhere and at any time.